Comparative Effect of Calcium Mesoporous Silica Versus Calcium and/or Fluoride Products on the Reduction of Erosive Tooth Wear and Abrasive Enamel Lesion - Isabella Barbosa dos Santos Justino; Adílis Kalina Alexandria; Fernanda Michel Tavares Canto; Karla Lorene de França Leite; Thiago Isidro Vieira; Lucio Mendes Cabral; Raphael Ferreira da Silva; Lucianne Cople Maia (Association of Support to Oral Health Research (APESB), 2022)
Objective: To evaluate the effect of a calcium nanocompound on the reduction of erosive tooth wear and abrasion. Material and Methods: Bovine enamel specimens (BE), were randomly assigned to the following groups (n = 10): G1 = Calcium mesoporous silica nanoparticles (Ca2+MSNs); G2 = casein phosphopeptide- amorphous calcium phosphate (CPP-ACP, 2% CPP-ACP, GC®); G3 = casein phosphopeptide-amorphous calcium fluoride phosphate (CPP-ACFP, 2% CPP-ACP + 900 ppm F-, GC®); G4 = sodium fluoride NaF (900 ppm F-, positive control); and G5 = distilled and deionized water (negative control). Each product was applied to the exposed area for one minute, three times per day for three consecutive days, and followed by the immersion of the specimens in Sprite Zero™ - a low-pH solution (2.58) for five minutes (Coca-Cola™). After the first and last erosive challenges of the day, the specimens were submitted to abrasion in a toothbrush machine for 15 seconds (200 g/BE). The specimens were analysed using 3D non-contact optical profilometry, with tooth structure loss (TSL) measurements and scanning electron microscopy (SEM). TSL values were analysed by Kruskal-Wallis and Mann-Whitney tests (p<0.05). Results: There were no significant differences between G1 (10.95 µm) and G3 (10.80 µm) treatments for TSL values; however both resulted in significantly reduced TSL values compared with the G5 (16.00 µm) (p<0.05). The G4 (12.26 µm) showed no statistically significant difference when compared to the G5 (16.00 µm). The groups G1 and G3 presented higher surface preservation than the G5. Conclusion: Ca2+MSNs was effective for reducing tooth surface loss caused by erosive tooth wear and abrasion.